First Pass Effect and Location of Occlusion in Recanalized MCA M1 Occlusions - Salahuddin, Hisham; Rao, Rahul R.; Zaidi, Syed F.; Prologo-Richardson, Paige; Khalid, Fatima; Saju, Linda; Taqi, Muhammad Asif; Burgess, Richard R.; Jumaa, Mouhammad A. (Frontiers in Neurology, 2022)
Background The first pass effect has been shown to improve clinical outcomes in patients with middle cerebral artery (MCA) M1 occlusions. Objective To determine the rates of first pass effect in MCA M1 occlusions and determine if proximal or distal location of occlusion modified clinical outcomes. Methods Patients with recanalized MCA M1 occlusions who underwent endovascular thrombectomy (EVT) were reviewed to determine the effect of first pass effect (FPE) and location of occlusion on clinical outcomes. MCA occlusions were classified as proximal if they included the first two thirds of the MCA and involved the lenticulostriate vessels, or distal if they did not. Results We included 261 patients of which 27% achieved FPE. Of the cohort, there were 91 (35%) proximal MCA occlusions and 170 (65%) distal MCA occlusions. Baseline demographics and treatment time metrics were comparable across both groups. There was a trend toward good clinical outcome in patients with or without a FPE (60 vs. 46%; p = 0.06), however a higher rate of excellent clinical outcome was noted in patients with FPE (46 vs. 30%; p = 0.02). When compared by location, patients with distal MCA occlusions had a higher rate of excellent clinical outcome (40 vs. 25%; p = 0.02). Multivariable analysis showed that distal MCA occlusion was the strongest predictor of an excellent clinical outcome and first pass effect. Conclusion Patients with MCA M1 occlusions with FPE have a higher rate of excellent clinical outcomes compared to those who did not. Location of MCA occlusion appears to modify rates of first pass effect and excellent clinical outcomes.